IDDF2019-ABS-0184 Role of adherent-invasive E. coli in inflammatory bowel disease – epidemiology, genetics and therapeutics. (June 2019) - Xu, Zhilu; Yang, Keli; Zhang, Jingwan; Zuo, Tao; Chevarin, Caroline; Chu, Lok Cheung; Chan, Francis; Sung, Joseph; Yu, Jun; Barnich, Nicolas; Wong, Sunny Hei; Ng, Siew Chien
Abstract : Background: Adherent-invasive Escherichia Coli (AIEC) colonizes mucosa of patients with Crohn's disease (CD). Fecal microbiota transplantation (FMT) has been reported to be effective in treating CD but the response rates are variable. We investigated the prevalence of AIEC in Chinese population and explored the impact of AIEC on FMT efficacy. Methods: AIEC strains were isolated from ileal tissues of Chinese Crohn's disease patients (n=64) and healthy subjects (n=53) by selection culture and protection assay in Intestine-407 cell lines and their genomes analysed . Effect of AIEC on FMT was assessed in C57BL/6 wild type DSS-colitis model. Level of AIEC colonization was assessed by selective culture and Fluorescence in situ hybridization. Human ileal tissue and mice feces were collected for 16S rRNA sequencing. Results: Prevalence of AIEC was significantly higher in mucosa of CD subjects than healthy controls (p<0.05). Significant loss of Megamonas and Veillonella was observed in AIEC-positive ileal tissues, compared with AIEC-negative and healthy tissues. The majority of AIEC isolates belonged to B2 phylogroup. 43.9% of AIEC isolates were multi-drug-resistant. The Chinese AIEC isolates possessed a significantly higher prevalence of Quinolone-, Macrolide-, Sulphonamide-, Trimethoprim-, and Tetracycline- resistant genes, compared with previously reported strains. These antibiotics resistant strains possessed significantly higher invasion properties than did non-resistant strains. In mice, FMT was not able to eradicate AIEC from the colon. After FMT, K12 (a noninvasive E. coli strain) - colonised mice, but not AIEC-infected mice, showed ameliorated colitis with elongated colon, improved colonic histology and decreased fecal Lcn-2 levels. FMT increased microbial diversity in K12-colonised mice but not in AIEC-infected mice. The proportion of donor-derived microbes in K12-colonised mice was significantly higher than in AIEC-infected mice, where a lack of engraftment of Fecalibacterium prausnitzii, Akkermansia muciniphila and Allobaculum was seen in AIEC-infected mice. Conclusions: AIEC is a risk factor for CD in the Chinese population. The presence of AIEC was sufficient to compromise the efficacy of FMT by hindering the engraftment of beneficial bacteria, leading to incomplete recovery of inflammation.